سنسنجی، پترولوژي، ژئوشیمی و تکتونوماگماتیسم سنگهاي حدواسط و مافیک کمپلکس پلوتونیک برنورد (شمالغرب بردسکن) - Monazzami Bagherzadeh, R. (2018)
The study area is located in the northeast of Iran (the Khorasan Razavi province) and 28 km northwest of Bardaskan city and in position of 57˚ 46΄ to 57˚ 52΄ latitude and 35˚ 21΄ to 35˚ 24΄ longitude. The study area is a part of Taknar zone. The Taknar geological-structural zone is situated in the north Central Iranian microcontinental and it is a part of Lut block (Fig.1). Taknar plutonic complex that is situated in the Taknar structural zone is located in the northern part of Iranian microcontinent. Chemical analysis of REE and minor elements of samples of the Bornaward diorites and gabbro’s took place in the ACME Lab. in Vancouver, Canada, by the ICP-MS method (Table. 1). For the Bornaward diorite dating by the U-Pb method, zircon grains of material remaining in the sieve, Bromoform were isolated from light minerals by cleaning and were isolated with a minimum size of 25 microns, and then studies took place in the Crohn's Laser Lab Arizona (Gehrels et al., 2008). Measurement of Rb, Sr, Sm and Nd isotopes and (143Nd/144Nd)i , (87Sr/86Sr)i ratios and ƐNd (T=552), ƐNd (T=0), ƐSr (T=552) and ƐSr (T=0) took place in radioisotope Laboratory, University of Aveiro in Portugal. Geology of study area The study area forms the central part of the Bornaward plutonic complex. This complex is a granitoid assemblage including granite, granodiorite, tonalite and granophyre. The central part has been formed by intermediate and basic intrusive rocks such as diorite, quartz diorite and gabbro units (Fig. 2). From the genetic point of view, the intermediate and mafic rocks of the Taknar plutonic complex does not have any relationship with granitoid rocks of this assemblage, and they are related to a similar magmatic phase but are separated from this granitoid assemblage. However, these mafic and intermediate units are older than granitic units at the rim of the complex that are called Bornaward granite. The main minerals in the diorite and quartz diorite rocks are plagioclase and hornblende and we can see biotite in the quartz dioritic rocks. Quartz exists as tiny grains and anhedral and in the matrix rock. The amount of Quartz in the quartz diorites is 5 to 20%. Plagioclases usually have normal zoning and are highly altered to sericite. Most of the plagioclases were saussuritized. Altered minerals resulted from plagioclase and hornblende are sericite, epidote, chlorite, zoisite and clinozoisite.The main minerals in the gabbro are pyroxene, hornblende, and fine grains plagioclase. Minor minerals in the rocks are apatite, magnetite and other opaque. The main texture of intermediate and mafic rocks in this assemblage is medium granular to coarse grain and especially in the intermediate rocks and gabbro rocks, we can see scattered poikilitic, intersertal, sub-ophitic and porphyroid texture. The area diorite and gabbro is located locate in Tholeiitic and Calc-alkaline series (Fig. 9). Shand index (Al2O3/(CaO+Na2O+K2O)) is obtained under 1.1, in Metaluminous field (Fig. 7) and I-type granite field (Chappell and White, 2001). Based on the TAS diagram (Middlemost, 1985), all the diorite and gabbro samples are located in diorite, gabbro-diorite and gabbro-norite groups (Fig. 6). The diorite and gabbro show enrichment LREE and low ascending pattern ((La/Yb)N =1.40-6.12 and LaN =12.26-75.81). Measurement of U-Th-Pb isotopes of the Bornaward diorite zircons of BKCh-03 sample (Table 2) show that its age is related to 551.96±4.32 Ma ago (Upper Precambrian (Neoproterozoic) (Ediacaran). The (87Sr/86Sr)i and (143Nd/144Nd)i content of Bornaward diorite and gabbro rocks is located in the range of 0.7038 to 0.7135 and 0.51203 to 0.51214, respectively (Tables 3 and 4). It shows that the diorite and gabbro rocks can be affected by hydrothermal alteration because their (87Sr/86Sr)i is above (Fig. 16). The numeral amounts of ƐNd(T=552) of Bornaward diorite and gabbro are 2.0 to 4.0. The Bornaward diorite and gabbro rocks show a widespread enriched pattern of Rb, U, K, Pb, La and Th elements than chondrite, while Ba, Ti, Ta, Sr and Nb elements show reduction as a result of fractional crystallization (Fig. 11). The rocks of this complex are formed at the continental margin and VAG environment (Fig. 18) which is related to the subduction of the oceanic crust that exists between the Iranian microcontinent and the Afghan Block. This assemblage with age of Late Neoproterozoic is the result of extensive magmatism in the northern part of the Iranian microcontinent due to Katangahi orogeny event. The similar magmatism in the northern part of the Iranian microcontinent is existing as Khaf-Kashmar-Bardeskan volcanoplutonic belt. Based on the geochemical investigations, the magmatism of these rocks has been tholeiitic and calk-alkaline and have formed the coexistent rocks with I-type granites. Alumina saturation index for intermediate and mafic rocks of Bornaward complex is metalumina. These are medium-K rocks and enriched in the LILE such as Rb, Pb, U and Th while depleted of the Nb, Ti, Ta, Sr and Ba. Therefore, it shows that these rocks have resulted from the mixing by the lower crust. The low (87Sr/86Sr)i Bornaward diorite and gabbro rocks and the numeral amounts of Ɛ0Nd(present) of these rocks from -0.2 to 4.0 show that production of such intrusive masses can be attributed to the source of upper mantle or contaminated lower continental crust. Environment of formation of the intermediate and basic rocks of the Bornaward plutonic complex is active continental margin and volcanic arc environment.